Cyanidin Chloride inhibits ovariectomy‐induced osteoporosis by suppressing RANKL‐mediated osteoclastogenesis and associated signaling pathways. Issue 3 (7th September 2017) - Cheng, Jianwen; Zhou, Lin; Liu, Qian; Tickner, Jennifer; Tan, Zhen; Li, Xiaofeng; Liu, Mei; Lin, Xixi; Wang, Tao; Pavlos, Nathan J.; Zhao, Jinmin; Xu, Jiake
Abstract : Over‐production and activation of osteoclasts is a common feature of osteolytic conditions such as osteoporosis, tumor‐associated osteolysis, and inflammatory bone erosion. Cyanidin Chloride, a subclass of anthocyanin, displays antioxidant and anti‐carcinogenesis properties, but its role in osteoclastic bone resorption and osteoporosis is not well understood. In this study, we showed that Cyanidin Chloride inhibits osteoclast formation, hydroxyapatite resorption, and receptor activator of NF‐κB ligand (RANKL)‐induced osteoclast marker gene expression; including ctr, ctsk, and trap . Further investigation revealed that Cyanidin Chloride inhibits RANKL‐induced NF‐κB activation, suppresses the degradation of IκB‐α and attenuates the phosphorylation of extracellular signal‐regulated kinases (ERK). In addition, Cyanidin Chloride abrogated RANKL‐induced calcium oscillations, the activation of nuclear factor of activated T cells calcineurin‐dependent 1 (NFATc1), and the expression of c‐Fos. Further, we showed that Cyanidin Chloride protects against ovariectomy‐induced bone loss in vivo. Together our findings suggest that Cyanidin Chloride is capable of inhibiting osteoclast formation, hydroxyapatite resorption and RANKL‐induced signal pathways in vitro and OVX‐induced bone loss in vivo, and thus might have therapeutic potential for osteolytic diseases. Abstract : Cyanidin Chloride inhibits osteoclast formation, hydroxyapatite resorption, and receptor activator of NF‐kB ligand (RANKL)‐induced osteoclast marker gene expression; including ctr, ctsk, and trap . Cyanidin Chloride inhibits RANKL‐induced NF‐kB activation, suppresses the degradation of IkB‐a and attenuates the phosphorylation of extracellular signal‐regulated kinases (ERK). Cyanidin Chloride also abrogates RANKL‐induced calcium oscillations, the activation of nuclear factor of activated T cells calcineurin‐dependent 1 (NFATc1), and the expression of c‐Fos. Cyanidin Chloride protects against ovariectomy‐induced bone loss in vivo. Cyanidin Chloride is capable of inhibiting osteoclast formation, hydroxyapatite resorption and RANKL‐induced signal pathways in vitro and OVX‐induced bone loss in vivo, and thus might have therapeutic potential for osteolytic diseases.